Exploring the Peri-, Chemo-, and Regio-Selectivity of addition of Metal Oxides to Ketenes: a DFT computational study - Ahmed, Issahaku (2017)
A thesis submitted to the Department of Chemistry, College of Science, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirement for the award of the degree of Master of Philosophy in Physical Chemistry